The Analysis of Sanitation and Hygiene Application of Food Management Place in Restaurant Bengkulu City - Nurul Khairani; Santoso Ujang Effendi; Refti Febli Lestari; Yusran Fauzi (Jurnal Sains Kesehatan, 2019)
Restaurant is a commercial venue where the scope of its activities provide food and beverages to the public in the place of business. This restaurant arises and develops in line with the development of society in serving the needs of consumers. This if not supported by hygiene food processing and good sanitation conditions it will cause food poisoning or diseases such as diarrhea. The purpose of this research is to analysis of  sanitation and hygiene application of food management place in restaurant Bengkulu City. Type of research used is descriptive with qualitative method, Informant in this research amounted to 4 person that is, owner of restaurant A, owner of restaurant B, restaurant owner C, Head of Environmental Health Counseling Dinkes Kota Bengkulu. The instruments used are observation sheets and interview guides. Data analysis was done by collecting interview result data then described to describe applying sanitation hygiene in restaurant with Triangulation technique. The result of this research is the application of sanitation hygiene at restaurant A (776), B (721) and C (720) have fulfilled the health requirement which refers to Permenkes Number: 1098 / Menkes / SK / VII / 2003 so that the restaurant is sanitary hygiene and safe for public consumption, between input and process restaurants A, B, and C input it has been referring to the foundation and the existing regulations as well as the supervision of sanitarian power has been executed so that at the stage of the process have a good effect on the restaurant supported by the assessment of sanitarian power. It is expected that local health agencies to more often hold activities that are promotive and preventive about the importance of the application of hygiene sanitation food processing in restaurants. Keywords : hygiene, restaurant, sanitation